Community gifting groups on Facebook - Amaç Herdağdelen; Lada Adamic; Bogdan State (Journal of Quantitative Description: Digital Media)
We use de-identified data from Facebook Groups to study and provide a descriptive analysis of local gift-giving communities, in particular Buy Nothing groups. These communities allow people to give items they no longer need, reduce waste, and connect to local community. Millions of people have joined Buy Nothing groups on Facebook, with an increasing pace through the COVID-19 pandemic. Buy Nothing groups are more popular in dense and urban US counties with higher educational attainment. Compared to other local groups, Buy Nothing groups have lower Facebook friendship densities, suggesting they bring together people who are not already connected. The interaction graphs in Buy Nothing groups form larger strongly connected components, indicative of norms of generalized reciprocity. The interaction patterns in Buy Nothing groups are similar to other local online gift-giving groups, with names containing terms such as `free stuff" and `pay it forward". This points to an interaction signature for local online gift-giving communities.